(untitled) (International Journal of Engineering and Computer Science, 2018)
The ideology of the Internet of things has emerged due to the consolidation of multiple technologies. IoT devices are a part of the larger concept of home automation, also known as domotics. The application of Internet of Things in indoor environment monitoring and control has become a major area as people paying more attention to quality of environment. Intelligent solutions are proposed by studying key technologies of IoT. The system provides a new application for IoT.